Selective detection of amyloid fibrils by a dipole moment mechanism on dielectrode – Structural insights by in silico analysis. (March 2023) - Adam, Hussaini; Gopinath, Subash C.B.; Kumarevel, Thirumananseri; Arshad, M.K. Md; Adam, Tijjani; Sauli, Zaliman; Subramaniam, Sreeramanan; Hashim, Uda; Chen, Yeng
Abstract: Amyloid fibrils are associated with different neurodegenerative diseases, a final product of several protein aggregation pathways. Parkinson's disease is a type of amyloidosis, characterized by the accumulation and propagation of amyloid fibrils of alpha-synuclein. The detection of fibrils at low concentrations is critical for the diagnosis of Parkinson's disease. We report a novel technique for the selective detection of amyloid fibrils through a dipole moment on a dielectrode surface. A sensitive dielectrode sensor for detecting aggregation of alpha synuclein and works by interacting an antibody on two-electrode surface functionalized gold interdigitated electrode. For the physical characterization of the sensing surface and finger electrodes, high-power microscope, scanning electron microscope, and 3D-profilormeter were used. Electrical characterization was performed on the sensing surface by using Keithley 6487 picoammeter. Based on the stability analysis with various electrolytes solutions, the sensor was found to be stable from pH 3. Further, under optimal circumstances, a linear range of alpha synuclein fibril detection was from 100 aM to 100 pM [y = 5E-06x + 5E-06; R² = 0.9724], and the limit of detection was estimated to be 100 aM based on S/N = 3. This study was further anchored by molecular docking analysis with synuclein peptide (47−56). We predict that advancements in this direction will assist in clarifying the complex process posed by Parkinson's disease. Graphical Abstract: ga1 Highlights: Amyloid fibrils associated with neurodegenerative diseases, in aggregation pathways. Parkinson's disease is amyloidosis, formed by amyloid fibrils of alpha-synuclein. Monitored alpha synuclein aggregation on a gold-interdigitated electrode surface. Detection was at 100 aM, on linear concentrations with coefficient regression. Anchored by molecular docking with synuclein peptide(47−56), binding region displayed.